Animated Film " Lorong Waktu Si AA: Rafathar Cinta Batik Indonesia" As a Media to Instill a Sense of Love for Culture To Children - Kelvin Alfi Nurdiansyah (Jurnal Scientia, 2023)
Animation is a spectacle favored by children, however mature This more Lots spectacle that is not give impact positive for child. RANS Animation Studio is here with an animated series raised child theme love and proud with Indonesian culture. in study This writer will examine one of the episodes that presents LorongTime theme love deep Indonesian batik form animation For kids. methodology used is qualitative descriptive with method analysis and observation For analyze element conveyed batik culture in the animated film "Lorong Waktu Si AA: Rafathar Loves Indonesian Batik".